2020
DOI: 10.1017/s1049023x20001399
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Point-of-Care Ultrasound Education for the Recognition of Tension Pneumothorax by Paramedics in Prehospital Simulation

Abstract: Objective: The primary goal of this study was to determine if ultrasound (US) use after brief point-of-care ultrasound (POCUS) training on cardiac and lung exams would result in more paramedics correctly identifying a tension pneumothorax (TPTX) during a simulation scenario. Methods: A randomized controlled, simulation-based trial of POCUS lung exam education investigating the ability of paramedics to correctly diagnose TPTX was performed. The US intervention group received a 30-minute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…A further three were also rejected as they did not involve assessment for pneumothorax [ 30 , 32 , 34 ]. Of the remaining twelve studies included in qualitative synthesis [ 1 6 , 22 26 , 33 ], eight reported sufficient and appropriate data for inclusion in meta-analysis [ 1 6 , 22 , 24 ]. Figure 3 depicts this study selection process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A further three were also rejected as they did not involve assessment for pneumothorax [ 30 , 32 , 34 ]. Of the remaining twelve studies included in qualitative synthesis [ 1 6 , 22 26 , 33 ], eight reported sufficient and appropriate data for inclusion in meta-analysis [ 1 6 , 22 , 24 ]. Figure 3 depicts this study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…All twelve included studies were published between 2011 and 2020 [ 1 6 , 22 26 , 33 ]. Collectively, they reported on the interpretations of n = 1,936 images captured predominantly from trauma patients presenting in the pre-hospital and/or in-flight setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We've read the article by Khalil, et al entitled "Randomized Controlled Trial of Point-of-Care Ultrasound Education for the Recognition of Tension Pneumothorax by Paramedics in Prehospital Simulation" with great interest. 1 The investigated disease is one which timesensitive intervention has an enormous effect on patient mortality. Thus, getting better at prehospital management of tension pneumothorax becomes paramount of importance.…”
mentioning
confidence: 99%